Upaya Meningkatkan Pengenalan Huruf Pada Anak Dengan Metode Bermain Kartu Huruf (Studi Kelompok A TK Kemala Bhayangkari Ruteng) - Priska Benedikta Jenahat; Ni Komang Ayu Sri Lestari; Gaudensiana Delsi; Selfiana Wallu (Universitas Nusa Cendana, 2021)
One of the teaching areas for kindergarten children is learning the alphabet. The introduction to letters is crucially taught because if one of the language activities is reading, then the absolute requirement for a child to read is to recognize letters first. This article aims to explain the efforts that can be made to improve alphabet recognition using the method of playing letter cards. The problem investigated in this research is how to enhance the ability to recognize letters among children in Group A of TK Kemala Bhayangkari Ruteng. This study employs the Classroom Action Research technique, and the number of research subjects is 20 children, consisting of 8 females and 12 males. The research results indicate that the effort of alphabet recognition using the method of playing letter cards makes children more interested in the learning process activities and enhances their language skills. There is an improvement from Cycle I to Cycle II, and the learning process becomes more enjoyable for the children as they are delighted and actively engaged in playing and arranging the letter cards.